Pengukuran Perangkat Lunak dengan Menggunakan Metode Function Point : (Studi Kasus : Cashlez) - Wulandari, Yohana; Fatkha, Billah; Rizky, Soetam (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2021)
The mPOS (Mobile Point Of Sale) application is a system of accepting payments using a card, either a credit card or an application-based debit card on a smartphone that is connected to a card reader via Bluetooth. This research was conducted using the Function Point method. The Function Point method itself is an approach that functions to measure software functionality in order to estimate the size of the software and can then be used as an estimate of the cost and effort required to develop the system.